1996
DOI: 10.1021/bi951550q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model for the Regulation by Substrate of Intramolecular Electron Transfer in Trimethylamine Dehydrogenase

Abstract: The reaction of trimethylamine dehydrogenase (TMADH) with trimethylamine has been studied by rapid-scanning stopped-flow spectroscopy and steady-state kinetics. The covalently bound 6-S-cysteinylflavin mononucleotide (FMN) cofactor is initially reduced by substrate and exhibits a limiting first order rate constant of 230 s(-1) at pH 7.5 and 30 degrees C. One electron is then transferred intramolecularly from the reduced FMNH2 to the oxidized [4Fe-4S]2+ center. This reaction is biphasic, and the extent of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 28 publications
4
35
1
Order By: Relevance
“…The magnitude of these rate constants are generally consistent with the half-life for the fast phase at pH 7.7 of 1.5-2 ms reported by Beinert and co-workers (10) when the higher temperature utilized in this earlier study is taken into account. In a more recent study, however, the kinetic properties for the reductive half-reaction of TMADH have been reported that differ significantly from those reported here (19), with limiting rate constants for the fast phase of 230 s Ϫ1 at pH 7.5, 30°C (significantly smaller than those reported here). In addition, the present results indicate that the slower phases of the reaction exhibit excess substrate inhibition, while this more recent work reported hyperbolic substrate concentration dependence for both the intermediate and slow phases.…”
Section: Reductive Half-reaction Kinetics Of Tmadh With Trimethylamine-contrasting
confidence: 90%
See 3 more Smart Citations
“…The magnitude of these rate constants are generally consistent with the half-life for the fast phase at pH 7.7 of 1.5-2 ms reported by Beinert and co-workers (10) when the higher temperature utilized in this earlier study is taken into account. In a more recent study, however, the kinetic properties for the reductive half-reaction of TMADH have been reported that differ significantly from those reported here (19), with limiting rate constants for the fast phase of 230 s Ϫ1 at pH 7.5, 30°C (significantly smaller than those reported here). In addition, the present results indicate that the slower phases of the reaction exhibit excess substrate inhibition, while this more recent work reported hyperbolic substrate concentration dependence for both the intermediate and slow phases.…”
Section: Reductive Half-reaction Kinetics Of Tmadh With Trimethylamine-contrasting
confidence: 90%
“…An analogous mechanism has also been shown to account for the excess substrate inhibition observed with xanthine oxidase (31). We emphasize that this mechanism for excess substrate inhibition in the steady-state is a necessary consequence of the known properties of TMADH, and is distinct from a model in which a second, inhibitory, substrate-binding site is present in the enzyme, as has been suggested (19). We note that the x-ray crystal structure of TMADH in complex with the substrate analog TMAC gives no indication of the presence of a second substrate-binding site (24,32).…”
Section: Reductive Half-reaction Kinetics Of Tmadh With Trimethylamine-mentioning
confidence: 74%
See 2 more Smart Citations
“…Steady-state Kinetic Analyses-As reported previously, the steady-state kinetics of wild-type TMADH exhibit excess substrate inhibition (18,30,31). By contrast, Y169F TMADH exhibits well behaved steady-state behavior: no evidence for substrate inhibition was seen even at very high substrate concentrations (up to 45 mM; Fig.…”
Section: Resultssupporting
confidence: 56%